Preparation of monospecific anti-PAG antibodies for cattle pregnancy detection: use of synthetic peptides to improve specificity - Ruiz Álvarez, Jimena Inés (2011)
Fil: Fil: Ruiz Álvarez, Jimena Inés. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR-CONICET); Argentina